Structural Equation Modeling on Women’s Perceptions of Halal Cosmetics Based on The Development of TPB Framework Using Religiosity, Social Influence, Knowledge, and Brand Value - Utami, Meinarini Catur; Fetrina, Elvi (Bright Publisher, 2024)
Nowadays cosmetics play an important role for women to maintain their beauty. The statistics show that in 2018, there was an increase of 5.5 % in the cosmetics market globally compared to the previous year whereas the skincare product accounted for about 39% of the worldwide market. In Indonesia, it shows quite the same condition and it also shows that the trend of halal cosmetics has a quite big demand with which 58.3% of Indonesian women choose halal cosmetics. This study was continuous research from the previous one conducted by the authors in 2018 to find out whether there was an influence of religiosity on Indonesian Muslim women intentions and behavior in buying Korean cosmetics based on Halal issues. Based on previous research and other similar research, the researchers developed The Theory of Planned Behavioral (TPB) as the model with some additional variables including religiosity, social influence, knowledge, and brand value. In continuation, this paper determined whether women regardless of these variables are interested in halal cosmetics that showed through intention variable in TPB. The model with 7 proposed hypotheses was analyzed by using the Structural Equation Modeling (SEM) method and SmartPLS as a tool. The results based on the 600 women of college students (muslim and non-muslim) in Java showed that 6 hypotheses have significant influence toward the intention to use halal cosmetics.